Topological Dirac semimetal Na3Bi films in the ultrathin limit via alternating layer molecular beam epitaxy - Igor V. Pinchuk (APL Materials, 2018)
Ultrathin films of Na3Bi on insulating substrates are desired for opening a bulk bandgap and generating the quantum spin Hall effect from a topological Dirac semimetal, though continuous films in the few nanometer regime have been difficult to realize. Here, we utilize alternating layer molecular beam epitaxy to achieve uniform and continuous single-crystal films of Na3Bi(0001) on insulating Al2O3(0001) substrates and demonstrate electrical transport on films with 3.8 nm thickness (4 unit cells). The high material quality is confirmed through reflection high-energy electron diffraction, scanning tunneling microscopy, x-ray diffraction, and x-ray photoelectron spectroscopy.